'Joy, Joy, Joy, Tears of Joy'. A contribution to theological anthropology. Issue 3 (27th May 2017) - Bom, Klaas
ABSTRACT: The growing scholarly debate on emotions and the development of Pentecostal and Charismatic churches in the Global South are just two reasons that urge systematic theology to relate more concretely to faith experiences. Potkay and others present joy as a typical Christian emotion, but it is not a key theme in systematic theology, although it plays far more prominent a role in spiritual and practical theological works. In this paper, the author presents the understandings of joy from the perspectives of Blaise Pascal, A.A. van Ruler and Pentecostals from Ecuador and explores the implications for theological anthropology. Based on the study of these three perspectives, the author defends the thesis that joy offers a new focus in the field of theological anthropology that places different traditional theological perspectives on the human being in a fresh relation to each other and lays a foundation for a theological contribution to emotion studies.